Spatial Restoration Ecology: Placing Restoration in a Landscape Context. (14th November 2018) - Gilby, Ben L; Olds, Andrew D; Connolly, Rod M; Henderson, Christopher J; Schlacher, Thomas A
Abstract: Researchers on conservation planning and practice have increasingly recognized and adopted the pivotal role of landscape attributes in shaping the effectiveness of protected areas. However, the degree to which these concepts have been integrated into habitat restoration projects has not been quantified. We reviewed the global literature and found that landscape context was considered in fewer than one in eight restoration projects in the selection of restoration sites (11% of 472 projects). This figure was remarkably similar across terrestrial (10% of 243 projects), marine (13% of 89), and freshwater (13% of 164) ecosystems. Of the 54 restoration projects in which landscape context was considered in site selection, in just over half (56%), animal populations were reported to be larger or more diverse than in control areas. Tighter integration of concepts from spatial ecology and systematic conservation planning into restoration practice could improve the design, optimize placement, and enhance the ecological effectiveness of restoration projects in all ecosystems.